Analisis sitasi publikasi tentang repositori bidang studi perpustakaan pada Web of Science selama pandemi - Wardhana, Akhmad Kusuma; Ratnasari, Ririn Tri (Daluang: Journal of Library and Information Science, 2022)
Introduction. Library repositories are indispensable for academics during a pandemic. This study aims to analyze citation trends during a pandemic.Methodology. This study uses bibliometric methods to analyze metadata of publications on the Web of Science page. The samples collected were around 481 in the range of 2020-2022. Data were analyzed using Biblioshiny in R Studio.Results and discussion. The results found that the most citation trends were in journals with a medical scope. The journals with the most manuscripts are journals with a library scope. Meanwhile, the keywords with the most citations relate to the research methodology. Meanwhile, the number of citations during the pandemic is actually high, and even in journals with a medical scope, it can reach thousands every year.Conclusion. The citations related to repository publications in libraries are not only focused on journals with a library scope, but also focused on journals with non-libraries.